The Electrical Activity of Masseter and Anterior Temporal Muscles in Patients With Unilateral Cleft Lip and Palate. Issue 6 (September 2019) - Jahanbin, Arezoo; Ahrari, Farzaneh; Saeidi, Morteza; Moeinifar, Azam; Sharifi, Farid
Abstract : Abstract: This study aimed to determine the electrical activity of masseter and anterior temporal muscles in patients with unilateral cleft lip and palate (CLP) and compare it with healthy volunteers. The study involved 20 female patients (mean age 20 ± 4 years) with unilateral cleft lip and palate who had undergone lip and palate surgery in childhood and finished the first-phase orthodontic therapy with level and align teeth. Twenty age- and sex-matched volunteers with no cleft lip and palate were involved as controls. Electromyographic (EMG) signals of masseter and anterior temporal muscles were recorded at rest position, during swallowing and during maximum bite force (MBF). EMG signals at different test conditions were compared between the cleft and noncleft sides of CLP patients and between CLP patients and healthy individuals. The EMG potentials of masseter (rest, swallowing, MBF) and temporal (rest, MBF) muscles were significantly higher in the cleft than the noncleft side of CLP patients ( P value <0.001). Generally, patients with unilateral cleft lip and palate experienced a significant increase in the electrical activity of the masseter and temporal muscles in both sides compared to the control group ( P <0.05). In conclusion, patients with unilateral cleft lip and palate exhibit overall greater masticatory muscle activity compared to healthy individuals. The asymmetric masticatory function in subjects with unilateral cleft lip and palate may be associated with severe consequences such as asymmetric facial growth, implying the importance of early diagnosis and orthodontic treatment to achieve a favorable environment for balanced facial growth in CLP affected patients. Abstract : Supplemental Digital Content is available in the text